2016
DOI: 10.1073/pnas.1601077113
|View full text |Cite
|
Sign up to set email alerts
|

Bison phylogeography constrains dispersal and viability of the Ice Free Corridor in western Canada

Abstract: The Ice Free Corridor has been invoked as a route for Pleistocene human and animal dispersals between eastern Beringia and more southerly areas of North America. Despite the significance of the corridor, there are limited data for when and how this corridor was used. Hypothetical uses of the corridor include: the first expansion of humans from Beringia into the Americas, northward postglacial expansions of fluted point technologies into Beringia, and continued use of the corridor as a contact route between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 53 publications
9
133
0
2
Order By: Relevance
“…The age is consistent 633 with the Quaternary record of western Canada as a whole, where early post-LGM records of bison are 634 widely reported in the literature (e.g., Wilson et al 2008;Heintzman et al 2016), and the record 635 provides insight into the sparse faunal history of east-central Alberta and west-central Saskatchewan. 636…”
Section: Elaphus 513supporting
confidence: 77%
“…The age is consistent 633 with the Quaternary record of western Canada as a whole, where early post-LGM records of bison are 634 widely reported in the literature (e.g., Wilson et al 2008;Heintzman et al 2016), and the record 635 provides insight into the sparse faunal history of east-central Alberta and west-central Saskatchewan. 636…”
Section: Elaphus 513supporting
confidence: 77%
“…Populations of elk, bison, and caribou locally survived in Yukon through this period of dramatic ecological turmoil and remained in the Subarctic and Arctic through much of the Holocene. Fossil and ethnohistorical evidence demonstrates that native bison populations in Yukon were regionally extirpated roughly 400 years ago (Stephenson et al 2001;Heintzman et al 2016). Present day populations of elk and wood bison (B. bison athabascae) are now common in the boreal forest of southern Yukon and are the result of human-mediated reintroductions during the mid-20th century.…”
Section: Study Site and Regional Contextmentioning
confidence: 99%
“…Genetic studies based on mitochondrial DNA from Quaternary bison have shown that extant bison, B. bison, arose during the last glacial maximum from ancestors situated south of the continental ice sheets, and that B. bison mitochondrial variation falls within a much more diverse bison complex (including the steppe bison, B. priscus) that occurred both north and south of the ice sheets during the late Pleistocene (Shapiro et al 2004;Heintzman et al 2016;Froese et al 2017). As mitochondrial DNA sequences can distinguish B. bison from other bison taxa, they can be used to infer the systematic status and phylogeographic history of enigmatic bison specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In a phylogeographic study of North American bison, Peter Heintzman et al (31) advocate for a greater emphasis on paleoecology as a major driving force shaping contemporary phylogeographic patterns. Their example involves the purported role of an Ice Free Corridor as a plausible route for dispersal (of humans and other animals) between Beringia and more southerly areas of North America.…”
Section: Comparative Phylogeography In a Taxonomic Sensementioning
confidence: 99%
“…This general topic has already been addressed by several of the colloquium papers. For example, Bowen et al (19) explicitly link modern marine phylogeography to traditional biogeographic perspectives on biodiversity in the sea; Wakeley et al (23), Mehta et al (24), and others relate phylogeography to historical population demography, coalescent theory, and traditional population genetics; Edwards et al (27) explicitly weighed and contrasted comparative phylogeography with molecular phylogenetics and phylogenomics; Heintzman et al (31) and Prates et al (21), among others, advocated the incorporation of more paleoecology into phylogeography; and several authors touched upon the special relevance of phylogeographic findings for the field of conservation biology. The final paper in this colloquium provides one further example of how comparative phylogeography relates to yet another emerging biodiversity field.…”
Section: Comparative Phylogeography In a Conceptual Sensementioning
confidence: 99%